Canada and the Palermo Protocol of 2000 on Human Trafficking: A Qualitative Case Study. - Holden, Christie (Université d'Ottawa / University of Ottawa, 2013)
This study consists of a qualitative analysis on the subject of human trafficking in Canada. It is intended to explore the steps that have been taken to address the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, Supplementary Legislation to the Convention Against Transnational Organized Crime (2000c), also known as the Palermo Protocol, and examine Canada’s commitment to changing the international and domestic context in which human trafficking takes place. Through exploration of Canadian legislation, literature and prosecutions presented in Canadian courts between January 2005 and December 2011, this research aims to establish whether Canada has shown a commitment to ending and preventing the problem of human trafficking that is consistent with the Recommended Guidelines published by the office of the United Nations High Commissioner on Human Rights (2002). A nominal coding scheme was used to show in basic terms the level of commitment Canada is showing toward combating the issue of human trafficking, both internationally and domestically. Results indicate that while Canada has met minimum standards by implementing anti-trafficking legislation in 2005 which is consistent with the Palermo Protocol, the country is falling short of commitments to combat human trafficking due to inadequate victim protection measures, lack of standardized data collection procedures and insufficient efforts to combat and prevent the root causes of trafficking.
Keywords: Canada Transnational Organized Crime; Canada Human Trafficking; Canada Palermo Protocol